Sustainability Reporting Trends: A Systematic Literature Review - Masniatul Aulia; Lilik Purwanti (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze trends and directions in sustainability report research using the SINTA indexed journal database and Emerald Insight international journal publications. This study uses a Systematic Literature Review (SLR) approach by reviewing open access articles published between 2019 and 2025. This study uses a framework of legitimacy theory, stakeholder theory, agency theory, signaling, and institutional theory that includes empirical and conceptual studies. The results of the analysis show that most studies in Indonesia use a quantitative approach with data from company annual reports from the Indonesia Stock Exchange. On the other hand, articles from Emerald Publishing combine quantitative and mixed methods approaches based on GRI standards as a measure of sustainability. Theoretically, these results increase the relevance of legitimacy theory and stakeholder theory as conceptual foundations in sustainability report analysis. Practically, this study highlights the importance of SR implementation and monitoring as tools for corporate transparency and accountability